Anion radical [2 + 2] cycloaddition as a mechanistic probe: Stoichiometry- and concentration-dependent partitioning of electron-transfer and alkylation pathways in the reaction of the Gilman reagent Me2CuLi.LiI with bis(enones) - JINGKUI YANG; CAUBLE, David F; BERRO, Adam J; BAULD, Nathan L; KRISCHE, Michael J (Journal of organic chemistry, 2004)
Exposure of easily reduced aromatic bis(enones) 1a-1e to the methyl Gilman reagent Me(2)CuLi.LiI at 0 degrees C in tetrahydrofuran solvent provides the products of tandem conjugate addition-Michael cyclization, 2a-2e, along with the products of [2 + 2] cycloaddition, 3a-3e. Complete partitioning of the Gilman alkylation and [2 + 2] cycloaddition pathways may be achieved by adjusting the loading of the Gilman reagent, the rate of addition of the Gilman reagent, and the concentration of the reaction mixture. The Gilman alkylation manifold is favored by the rapid addition of excess Gilman reagent at higher substrate concentrations, while the [2 + 2] cycloaddition manifold is favored by slow addition of the same Gilman reagent at lower concentrations and loadings. Notably, [2 + 2] cycloaddition to form 3a-3e is catalytic in Gilman reagent. Kinetic data reveal that the ratio of 2a and 3a changes such that the cycloaddition pathway becomes dominant upon increased consumption of Gilman reagent. These data suggest a concentration-dependent speciation of the Gilman reagent and differential reactivity of the aggregates present at higher and lower concentrations. While the species present at higher concentration induce Gilman alkylation en route to products 2a-2e, the species present at lower concentration provide products of catalytic [2 + 2] cycloaddition, 3a-3e. Moreover, upon electrochemical reduction of the bis(enones) 1a-1e, or chemically induced single-electron transfer from arene anion radicals, the very same [2 + 2] cycloadducts 3a-3e are formed. The collective data suggest that [2 + 2] cycloadducts 3a-3e arising under Gilman conditions may be products of anion radical chain cyclobutanation that derive via electron transfer (ET) from the Me(2)CuLi.LiI aggregate(s) present at low concentration. These observations provide a link between the Gilman alkylation reaction and related ET chemistry and suggest these reaction paths are mechanistically distinct. This analysis is made possible by the recent observation that easily reduced bis(enones) are subject to intramolecular [2 + 2] cycloaddition upon cathodic reduction or chemically induced ET from arene anion radicals, and is herewith showcased as a novel method of testing for the intermediacy of enone anion radicals.